Sustainable intensification strategies: balancing productivity, quality, and profitability in agri-food systems with resource optimization - Dass, Anchal; San, Aye Aye; Jinger, Dinesh; Kumari, Kavita; Singh, Arjun; Singh, Teekam; Poonam, Annie; Paramesh, Venkatesh; Gupta, Gaurendra; Rajanna, GA; Kaur, Ramanjit; Shekhawat, Kapila; et al. (Frontiers in Agronomy, 2025)
ContextMeeting the rising global nutritional demands is a critical challenge due to population growth, increasing incomes, shrinking natural resources, and climate change. Enhancing crop productivity while ensuring sustainability requires innovative and efficient agricultural practices. The System of Crop Intensification (SCI), adapted from the System of Rice Intensification (SRI), offers a promising solution by optimizing agronomic management for various crops, such as wheat, millets, maize, sugarcane, rice, and soybean.Research questionThis review examines the potential of SCI in improving crop yields, profitability, and resource use efficiency. The primary research question is: How does SCI impact crop productivity, soil health, and farmers’ income compared with conventional farming methods?MethodsThe review synthesizes recent studies and field trials on SCI adoption across multiple crops and regions. Key agronomic modifications considered include wider planting geometry, improved water management, organic manure application, residue retention, and integrated weed management. The effects of SCI on yield, nutrient uptake, soil quality, resource-use efficiency and economic returns were analyzed.ResultsSCI practices have demonstrated a significant yield increase, often more than doubling production compared with conventional methods. The adoption of SCI has resulted in a 15%–25% yield improvement in major field crops, along with enhanced oil and protein content, increased nutrient uptake, and improved water-use efficiency. Although SCI involves higher initial production costs, the increased crop yields compensate for the expenses, leading to higher net returns for farmers.ConclusionsSCI is an effective and sustainable agronomic approach that enhances productivity while improving soil health and resource-use efficiency. The approach contributes to climate resilience and profitability, making it a viable option for small and marginal farmers. The observed improvements in soil–plant interactions indicate the need for further scientific exploration of the mechanisms driving these benefits.ImplicationsSCI provides an ecologically sustainable solution to global food security challenges. Its adoption at a wider scale can significantly increase farmer incomes, enhance soil fertility, and contribute to environmentally friendly farming practices. Encouraging research, demonstration, and policy support for SCI will be crucial in ensuring its widespread implementation and long-term success.